Factors critical to benefits realisation of IT/IS projects in the South African government - Matsio, Thato (Department of Computer Science, 2019)
Purpose – This research investigated factors critical to benefits realisation of IT/IS project in the South African Government. The aim of the research was therefore to establish a list of factors critical to benefits realisation of IT/IS projects in SA government by testing the applicability of Coombs (2015) factors and as well as testing factors identified in the literature. Method – In addition to the factors identified in Coombs (2015) study, a literature review was conducted to identify additional factors critical for benefits realisation in IT/IS projects and twenty-one factors were identified. A web-survey with twenty one (21) success factors was sent to IT stakeholders in SA government particularly the State Information Technology Agency to determine their relevance and importance in benefits realisation of IT/IS projects in SA government. Results – The research finding revealed that all four of Coombs (2015) study success factors were relevant. Two of the factors were amongst the top ten factors considered the most important factors rated by the IT stakeholders in SA government. It also revealed that all twenty-one factors were relevant, however the following ten (10) factors were considered the most important factors: Clear Project Mission, Effective Communication, Defined Project Scope, User/Client Involvement, Top Management Support, Competent Project Manager, Sufficient/Well allocated resources, Strong, and detailed project plan, Business Process Knowledge, and Governance Structure. Furthermore, the research also revealed nine (9) additional factors identified by the IT stakeholders and they include: Political Stability, Architecture, Supportive legislation and policies, Teamwork, Trust and Honesty, IT solutions aligned to global Trend, Social and Economic Impact on Citizen, System Integration, and Project Management Methodology. Practical Implications – The findings allowed for an establishment of twenty-one factors critical for benefits realisation in IT/IS projects in SA government. However, the findings and the research process had some limitations. The sample for the survey was chosen from a population of a single organisation. The outcome of the survey is not an accurate representation of the entire government. Therefore, further research might be required using a larger sample size spanning various and different levels of government. The research findings may also need to be confirmed with more qualitative methods.